AB1140-HPR Senior Rheumatologysts, Junior Rheumatologysts, Nurse Specialists and Patients with Similar Diseases – Four Sources of Information for Rheumatic Patient not Equally Valued, not Equally Used. (10th June 2014) - Dobroiu, M.; Vasile, D.; Ioan, C.; Aproianu, C.; Predeteanu, D.; Popescu, C.; Ursa, E.; Coroianu, C.; Stanescu, C.E.; Popescu, M.; Jercan, M.; Berghea, F.; et al.
Abstract : Background: Chronic rheumatic patients have to face various needs of communication throughout their illness. Their doctors, nurses and fellows suffering from similar diseases are the main oral sources of information. Based on their availability, perceived competence, presumed quality or easiness to access these sources are used to address the information needs. In order to improve their education of is important to know the way our rheumatic patients use these sources to fulfill their information needs. Objectives: To identify the patients' preference for a certain source of information in relation with their particular needs. Methods: A structured questionnaire developed to assess the preference for one of the four main source of information (senior & junior rheumatologists, nurse specialists and similar patients) in relation with 12 problems connected in 5 areas: diagnostic & treatment, alternative management, impact of disease, dealing with administrative obstacles and source of additional information. For each item we determined the level of preference as a mean of answers (on a 0 to 10 scale) we received. 205 rheumatic patients from five tertiary centers accepted to answer the questionnaire. SPSS 19.0 have been used for statistical analysis and a p<0.05 was considered significant. Results: The highest levels of preference (mean (SD)) for information given by specialized nurses have been computed for: additional source of information (7.3 (2.7)), future evolution of disease (7.2 (2.9)), impact of disease on personal life (7.1 (2.8)), seriousness of disease (6.9 (2.7)), adverse reactions to treatment (6.8 (2.7)). However in none of 12 problems the nurse was not the most preferred source of information and in just one case she was the 2nd best choice. Patients with lower levels of formal education and those from urban areas scored higher for nurses but did not changed the hierarchy. Nor the disease duration or the gender of responder have influenced the final results. Conclusions: The study reveals a potential need for strengthening the role of specialized nurse as a quality source of information for chronic rheumatic patients in the context of her increasing role in long-term management. However, the areas we identified in this study as being higher rated for nurses might benefit from their input even sooner. Specialized nurses should develop their own action plan to solve this issue in the benefit of our patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2689